2013
DOI: 10.5194/angeo-31-359-2013
|View full text |Cite
|
Sign up to set email alerts
|

Statistical characteristics of PMWE observations by the EISCAT VHF radar

Abstract: In the present paper ~ 32.5 h of EISCAT VHF PMWE observations were analyzed with focus on spectral properties like spectral width, doppler shift and spectral shape. Examples from two days of observations with weak and strong polar mesosphere winter echo (PMWE) signals are presented and discussed in detail. These examples reveal a large variability from one case to the other. That is, some features like an observed change of vertical wind direction and spectral broadening can be very prominent in one case, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 60 publications
1
9
0
Order By: Relevance
“…Vast efforts have been made to derive turbulence energy dissipation field in the MLT by means of radar soundings (e.g., Hocking, 1983Hocking, , 1985Hall et al, 1998Hall et al, , 2003Strelnikova and Rapp, 2013;Lübken, 2014). It is understood that the radar-based turbulence measurements can be biased by both instrumental effects as well as some GWs' contributions to the measured variances of the wind fluctuations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vast efforts have been made to derive turbulence energy dissipation field in the MLT by means of radar soundings (e.g., Hocking, 1983Hocking, , 1985Hall et al, 1998Hall et al, , 2003Strelnikova and Rapp, 2013;Lübken, 2014). It is understood that the radar-based turbulence measurements can be biased by both instrumental effects as well as some GWs' contributions to the measured variances of the wind fluctuations.…”
Section: Discussionmentioning
confidence: 99%
“…To better compare the in situ and radar turbulence measurements, we plotted mean energy dissipation rates derived between 80 and 90 km heights from the rocket-borne and radar This indicates that the high ε values, derived from the EISCAT measurements in this study or, for example, by Strelnikova and Rapp (2013) are likely realistic. Another important remark regarding these measurements is that the mean ε values differ from high-resolution instantaneous measurements by orders of magnitude.…”
Section: Turbulence Measurementsmentioning
confidence: 99%
“…(We should mention that the validity of Eq. (13), which relates the spectral width of the radar echo to the turbulent dissipation rate, has been discussed by Strelnikova and Rapp (2013) for the EISCAT VHF radar for the case when MSPs are present. They noted that there is no theoretical justification for the equation in this case.…”
Section: Discussionmentioning
confidence: 99%
“…As indicated by the name, it is a weak radar echo that is commonly observed in the polar regions during nonsummer periods. Recent studies on PMWE have reported its characteristics as follows (Kirkwood, ; Latteck & Strelnikova, ; Strelnikova & Rapp, ; Zeller et al, ). PMWE is typically scattered and observed from 55 to 85 km.…”
Section: Introductionmentioning
confidence: 99%